Proses Pencokelatan Jaringan Adiposa - Afifa Radhina (Indonesian Journal of Health Science, 2021)
Obesity is a common, serious, and detrimental condition. In 2014, more than 1.9 billion adults were overweight. Obesity is associated with many diseases and the increase in obesity has become a major health problem. Obesity is caused by an imbalance between energy intake and energy consumption. Adipose tissue is an endocrine organ that secretes many hormones and cytokines that can affect metabolism. There are two types of adipose tissue in the body with different functions, namely white adipose tissue and brown adipose tissue. White fat has a major function in storing energy and is increased in obesity, while brown fat produces heat (thermogenesis) and then increases energy consumption. Therefore, brown fat and the induction of brown fat-like properties in white fat, have been considered as targets in the fight against obesity. The complex process of cell differentiation leading to the appearance of active brown adipocytes has been identified. There are classic brown adipocytes and cream adipocytes. Beige adipocytes are brown adipocytes that appear on precursor cells of white adipose tissue due to stimuli. Brown adipocytes are equipped with mitochondria containing uncoupling protein 1 (UCP1), which, when activated, controls ATP synthesis and stimulates respiratory chain activity. The browning process of adipose tissue is controlled by factors such as exercise. Obesitas merupakan keadaan yang umum, serius, dan merugikan. Tahun 2014, lebih dari 1,9 milyar orang dewasa mengalami kelebihan berat badan. Obesitas berasosiasi dengan banyak penyakit dan peningkatan obesitas telah menjadi masalah kesehatan utama. Obesitas disebabkan oleh ketidakseimbangan antara energi yang masuk dan konsumsi energi. Jaringan adiposa dalam tubuh ada dua tipe yang fungsinya berbeda, yakni jaringan adiposa putih dan jaringan adiposa cokelat. Lemak putih berfungsi utama dalam menyimpan energi dan meningkat pada obesitas, sedangkan lemak cokelat menghasilkan panas (termogenesis) dan kemudian meningkatkan konsumsi energi. Oleh karena itu, lemak cokelat dan induksi sifat seperti lemak cokelat pada lemak putih, telah dipertimbangkan sebagai target dalam melawan obesitas. Tujuan penelitian ini adalah untuk mengetahui proses pencoklatan jaringan adiposa putih. Metode penelitian yang digunakan adalah metode penelusuran ilmiah. Hasil penelitian diperoleh bahwa adiposit krem merupakan adiposit cokelat yang muncul pada sel prekursor dari jaringan adiposa putih karena adanya stimuli. Adiposit krem sama seperti adiposit cokelat dilengkapi dengan mitokondria yang mengandung uncoupling protein 1 (UCP1), yang ketika teraktivasi akan mengendalikan sintesis ATP dan menstimulasi aktivitas rantai respirasi. Beberapa regulator seperti PPAR γ, PGC-1α, dan PRDM16 muncul sebagai pelaku utama dalam proses diferensiasi adiposit krem.